COASTAL SEDIMENT UTILIZATION TO UPTAKE P, K NUTRIENTS AND THE YIELD OF CORN (Zea mays L.) PLANT ON TAILINGS MEDIA - Maspuroh, Siti; Suswati, Denah; Hazriani, Rini (Jurnal Sains Pertanian Equator, 2014)
Maize (Zea mays L.) is agricultural commodity that many has benefits for human and animals life. Increase of corn in production can be land through expansion (extension) with the former to land use Gold Mining Without Permission (GMWP) KalBar who reached 4922.3 ha and was expected to grow continue each years. Gold mined of land (tailings) has a pH of soil and low on nutrients that it can support the growth and of corn plants. Coastal sediment containing P, K, Ca, Mg and Na nutrients were high as to increase the pH of soil, adding nutrients and base saturation. This research was conducted to determine the effect coastal sediment to uptake P, K nutrients and the yield of corn on tailings media. Design to this research is Completely Randomized Design treatment that consist of 7, 3 replicated and 2 sets of plant. Dose of coastal sediment on treatment is no treatment (L0), 140 g/polybag (L1), 280 g/polybag (L2), 420 g/polybag (L3), 560 g/polybag (L4), 700 g/polybag (L5) and 860 g/polybag (L6). Parameters observed is uptake P, K and on top dry weight of plant and dry weight per plant. The yield indicate general of coastal sediment can increase the yield maize of crop is 6,8 ton/ha compared to control. Keyword : Corn, coastal sediment, tailings